Integrating land-use planning and transportation- policy formulation in the Belfast Metropolitan Area - McEldowney, Malachy; Scott, Mark; Smyth, Austin (Irish Geography, 2014)
Much of the interest in sustainable cities relates to the inexorable rise in the demand for car travel and the contribution that certain urban forms and land-use relationships can make to reducing energy consumption. Indeed, this demand is fuelled more by increased spatial separation of homes and workplaces, shops and schools than by any rise in trip making. This paper evaluates recent efforts to integrate land-use planning and transportation policy in the Belfast Metropolitan Area by reviewing the policy formulation process at both a regional and city scale. The paper suggests that considerable progress has been made in integrating these two areas of public policy, both institutionally and conceptually. However, concerns are expressed that the rhetoric of sustainability may prove difficult to translate into implementation, leading to a further dislocation of land-use and transportation.